2007
DOI: 10.1029/2006jd007584
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition observed over the mid‐Atlantic and the detection of pollution signatures far from source regions

Abstract: The atmospheric composition of the central North Atlantic region has been sampled using the FAAM BAe146 instrumented aircraft during the Intercontinental Transport of Ozone and Precursors (ITOP) campaign, part of the wider International Consortium for Atmospheric Research on Transport and Transformation (ICARTT). This paper presents an overview of the ITOP campaign. Between late July and early August 2004, twelve flights comprising 72 hours of measurement were made in a region from approximately 20 to 40°W and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 36 publications
7
74
0
Order By: Relevance
“…For air arriving at CVAO in summer, decomposition of PAN can be considered to be effectively complete. Previous measurements of PAN in the mid-Atlantic indicated mixing ratios ranging from more than 3 ppbv above 7 km, to below 5 pptv in the marine boundary layer (Lewis et al, 2007). This study showed that the presence of NO x in the early and later stages of a plume trajectory typically resulted in significant elevation in ozone in the mid Atlantic, albeit with very low in situ NO x detected when measurements were made in the MBL.…”
Section: Greenhouse Gasesmentioning
confidence: 44%
“…For air arriving at CVAO in summer, decomposition of PAN can be considered to be effectively complete. Previous measurements of PAN in the mid-Atlantic indicated mixing ratios ranging from more than 3 ppbv above 7 km, to below 5 pptv in the marine boundary layer (Lewis et al, 2007). This study showed that the presence of NO x in the early and later stages of a plume trajectory typically resulted in significant elevation in ozone in the mid Atlantic, albeit with very low in situ NO x detected when measurements were made in the MBL.…”
Section: Greenhouse Gasesmentioning
confidence: 44%
“…Long-range transport Research over the past two decades has clearly shown that ozone and ozone precursors are regularly exported from their emission source, or point of production, to receptor regions far downwind on the regional, intercontinental and even hemispheric scale (see reviews by Stohl and Eckhardt, 2004;Monks et al, 2009;Council, 2009b;HTAP, 2010). These transport pathways are predominantly from west to east at mid-latitudes, with in situ and satellite-based observations showing that pollution plumes (anthropogenic and biomass burning) not only travel from North America to Europe, or from East Asia to North America, but can also circle the globe (Jacob et al, 1999;Jaffe et al, 1999;Lewis et al, 2007;Wild et al, 2004).…”
Section: Transport and Mixing Processesmentioning
confidence: 99%
“…Table 2 details the available isoprene observations for model evaluation fitting these criteria. A small number of aircraft observations are available from the ITOP experiment over the mid North Atlantic Ocean (Lewis et al, 2007), where the aircraft sampled near-surface marine air north-west and south-east of the Azores in July 2004. Limited periods of more frequent measurements are available from ship cruises in the marine surface atmosphere of the Western North Pacific during May 2001 (Matsunaga et al, 2002) and the remote Southern Indian Ocean during December 1997 (Yokouchi et al, 1999).…”
Section: Evaluation Of Marine Isoprene Emissionsmentioning
confidence: 99%